1997
DOI: 10.1111/j.1365-2222.1997.tb01168.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of allergy in high‐risk children

Abstract: Allergic disease in childhood is to a large degree determined before birth or during infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 40 publications
5
74
1
Order By: Relevance
“…For dog sensitization in this study, too few were sensitized to comment [2]. Two studies, from the United Kingdom [10] and the United States [11••], reported on allergic sensitization. The UK study found a decrease in the risk for allergic sensitization using immunoglobulin E (IgE) (AlaTOP multiallergen screen) for those with a cat or dog in infancy; the authors comment that the effect was greater for dogs than cats but do not present this data separately.…”
Section: Birth Cohort Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…For dog sensitization in this study, too few were sensitized to comment [2]. Two studies, from the United Kingdom [10] and the United States [11••], reported on allergic sensitization. The UK study found a decrease in the risk for allergic sensitization using immunoglobulin E (IgE) (AlaTOP multiallergen screen) for those with a cat or dog in infancy; the authors comment that the effect was greater for dogs than cats but do not present this data separately.…”
Section: Birth Cohort Studiesmentioning
confidence: 94%
“…Two found no association [6,9], and one reported a reduced risk among dog owners [7••]. For sensitization to other allergens, one found no association [5••], and three found a reduced risk with dogs or cats [10], with two or more required in one study [7••], or dogs alone [11••].…”
Section: Birth Cohort Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…During the last decades, 31 prospective birth cohort studies have been carried out to investigate the relations between potential risk factors and atopic disorders. More recently, a growing interest has been shown in testing the impact of environmental exposure on atopic diseases: these studies have been conducted worldwide [12][13][14][15][16][17][18], with half of them in European countries [8,[19][20][21][22][23][24][25][26][27]. But to the best of our knowledge, no data from longitudinal birth cohort study on relations between French environmental conditions and behavioural habits and atopic manifestations occurrence are available today.…”
Section: Introductionmentioning
confidence: 98%
“…However, these studies have also not yielded completely consistent results, and the controversy continues. Some of these studies indicate that early exposure to animal allergens, especially in the first year of life, may protect against the development of allergic disease in childhood [5••], whereas others have found that early pet exposure does not seem to influence the development of allergic sensitization [6][7][8]. In this article, we review the recent data on early exposure to animal allergens in regard to the development of allergic sensitization and atopic disease.…”
Section: Introductionmentioning
confidence: 98%